Analysis The Effectiveness of E-Learning in Increase Skills Digital Literacy and Shaping Discipline Study Students - Margareta, Meliana (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2025)
The rapid development of digital technology in the era of Society 5.0 has transformed students’ learning methods, including through the use of E-Learning. However, at SMK PGRI 13 Surabaya, there are still students who experience difficulties in operating platforms such as Google Classroom, which impacts their digital literacy and learning discipline. This phenomenon highlights the importance of analyzing the effectiveness of E-Learning as a digital learning medium. This study aims to determine the effect of E-Learning use on improving students’ digital literacy skills and shaping their learning discipline. The research is based on the theory of digital literacy and the theory of learning discipline. A correlational quantitative approach was used, employing a survey method. The sample consisted of 250 students from grades X to XII at SMK PGRI 13 Surabaya. The research instruments included the E-Learning Scale, Student Digital Literacy Measure, and ABS. Data were analyzed using descriptive statistics, Pearson correlation, and linear regression tests. The results showed a positive and significant relationship between E-Learning and digital literacy (r = 0.678; p < 0.05) as well as learning discipline (r = 0.592; p < 0.05). In addition, a strong relationship was found between digital literacy and learning discipline (r = 0.641; p < 0.05). Regression analysis indicated that E-Learning contributed 46% to improving digital literacy and 35.1% to students’ learning discipline.